Effect of Monochromatic Red Light of Different Intensities during Growth on Production Efficiency of Vinblastine in Catharanthus roseus with Ultraviolet A Light Irradiation - WATANABE, Hiroyuki; FUKUYAMA, Taro; OKUSU, Takatoki; OHASHI-KANEKO, Keiko (Environment control in biology, 2023)
This study aimed to evaluate that the effect of the biomass and the vinblastine precursor concentrations in Catharanthus roseus before ultraviolet A (UV-A) light irradiation on vinblastine accumulation in the leaves for commercial vinblastine production in a plant factory with artificial light (PFAL). C. roseus seedlings were cultivated under monochromatic red lights with different photosynthetic photon flux densities of 150 (low) and 300 (high) μmol m-2 s-1 for 28 d and then were irradiated 5 W m-2 UV-A light with monochromatic red lights with their different intensities for 5 d. The leaves dry weight was higher in high intensity treatments compared to low intensity treatments. After UV-A irradiation, the vinblastine concentration were approximately two times higher in the low intensity treatment than in the high intensity treatment. However, the vinblastine yield, a product of leaves dry weight and vinblastine concentration, did not have the great difference between the low and high intensity treatments. This study suggested that a suitable method to produce vinblastine using the PFAL was to apply the low intensity of monochromatic red light before UV-A light irradiation because the light use efficiency of vinblastine production was higher in the low intensity treatment than in high intensity treatment.